Cadastral Surveys: addressing territorial disputes in Somaliland - Drysdale, John (Technical Centre for Agricultural and Rural Cooperation, 2004)
John Drysdale describes how natural area codes and a GIS database are enabling farmers in war-torn Somaliland to gain legal title to their land.